Peran Inovasi Pendidik dalam Inovasi Pembelajaran di Era Digital - Nilam; Alfina; Umam, Khoyibul; Sudrajat, Yayan (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2022)
The role of educators in learning innovation is very important, judging from the development of the era which is currently an all-digital model. Educators are required to be able to pursue that development by applying it to the learning process in schools. This effort is to attract and make it easier for students to receive the material presented by educators. The method used in this study is a literature study with a descriptive quantitative type of research with a literature review. In this study, the authors used various written sources such as articles, journals, and documents relevant to the study in this study. The results of the study show that innovation is a process of renewal and change. In the field of education, innovation is needed to continue to develop following other fields. The use of this technology has a positive and negative impact, but the impact can be focused on positive impacts and minimize the negative impact if there is good cooperation from various parties so that the use of technology is in accordance with its goals.